The Signification of Flora in the Poem of Zurinah Hassan According to the Malay Theory of Methodology - Abd Rahman, Samsina; Yusoff, Muhammad Fadzil (2010)
Flora is God’s unique creation. According to the Qur’an, its life processes and beauty maintain the right balance and prove the power of Allah SWT. However, for a poet, observing and studying nature becomes more interesting when viewed through analogy or metaphor and through interpretation and meaning. In this study, the signiﬁcation of ﬂora in ﬁve collections of poems by Zurinah Hasan, Sesayup Jalan (1974), Di Sini Tiada Perhentian (1977), Keberangkatan (1985), Pujangga Tidak Bernama (1994), and Kumpulan Puisi Salasilah (2005), will be examined. Signiﬁcation and thought are found in all aspects of life. Flora can be classiﬁed as jungle or rice plants, and as trees and branches, ﬂowers and fruits. These explain phenomena that represent human life such as poverty, character, behaviour, love, femininity, national identity, politics, leadership, and the strength and resilience of the will to live, centred around life in the past and present, as well as historical remains. The analysis in this paper is done using the Malay Theory of Methodology, which places importance on goodness and usefulness, justice in society, beauty in art, symbols (signs) and their meaning, and, most importantly, increasing one’s love for and belief in Allah.